FERTILISASI DAN DAYA TETAS TELUR IKAN TAWES (Puntius javanicus) DARI SPERMA PASCA PENYIMPANAN PADA TEMPERATUR 4oC - Nuri Lismawati; Afrizal Hendri; Mahendra Mahendra (Universitas Teuku Umar, 2016)
This research aims to know the level of fertilization and hatching rate of tawes fish eggs (Puntius javanicus) after cryopreservation sperm in temperature 4oC. This research has been carried out in the mini laboratory (Meunasah Krueng Village of Beutong Subdistrict Nagan Raya Regency) on 19-20 August 2015. This research is both experimental, using a complete Randomized Design with 5 treatments and 3 replicates. Sperm that is used is the result of storage with the dilution of physiological NaCl and green coconuts water including P1 0% NaCl only, P2 3%, P3 5%, P4 7% and P5 9%. The results showed that the addition of green coconut water on sperm storage provides a real effect against fertilization and hatching rate of tawes fish eggs (p < 0.05). The highest levels of fertilization found in the treatment of P4 (64.3%, 0.7 mL of diluent in green coconut water + physiological NaCl solution), while the lowest fertilization found on P1 registration (25%, physiological NaCl solution). For the level of hatching rate, the highest value is found in the treatment of P4 (61.7%), and the lowest is present on the P1 registration (14.3%).